Engineering the development of democratic citizenship education curriculum in the global era: A few perspectives from theoretical frameworks - Suyato Suyato (Jurnal Civics: Media Kajian Kewarganegaraan)
There are weaknesses both from the perspective and effectiveness of Citizenship Education (CE) which are too oriented towards domestic problems in the context of facing global challenges and problems. Today it is necessary to change the orientation of the Civics curriculum which is globally oriented. In other words, it is necessary to engineer the Civics curriculum development. This paper attempts to present theoretical frameworks for engineering the development of a democratic and globally oriented Civics curriculum. There are at least six theoretical frameworks, namely the Birdcage Theory, Crystal Theory, Tree Theory, DNA Theory, Mushroom Theory, and Amoeba Theory. The six theories have different views, implications, and recommendations in curriculum engineering, including the Civics curriculum. This paper ends with the author's recommendations after considering both the strengths and weaknesses of the six theoretical frameworks.